Supersymmetric electroweak cosmic strings - Edelstein Glaubach, José Daniel (1997)
We study the connection between N52 supersymmetry and a topological bound in a two-Higgs-doublet system with a SU(2)xU(1)yxU(1)y' gauge group. We derive the Bogomol’nyi equations from supersymmetry considerations showing that they hold provided certain conditions on the coupling constants, which are a consequence of the huge symmetry of the theory, are satisfied. Their solutions, which can be interpreted as electroweak cosmic strings breaking one-half of the supersymmetries of the theory, are studied. Certain interesting limiting cases of our model which have recently been considered in the literature are finally analyzed.